Live vaccines after pediatric solid organ transplant: Proceedings of a consensus meeting, 2018. (9th September 2019) - Suresh, Sneha; Upton, Julia; Green, Michael; Pham‐Huy, Anne; Posfay‐Barbe, Klara M.; Michaels, Marian G.; Top, Karina A.; Avitzur, Yaron; Burton, Catherine; Chong, Pearlie P.; Danziger‐Isakov, Lara; Dipchand, Anne I.; et al.
Abstract: Growing evidence suggests receipt of live‐attenuated viral vaccines after solid organ transplant (SOT) has occurred and is safe and needed due to lapses in herd immunity. A 2‐day consortium of experts in infectious diseases, transplantation, vaccinology, and immunology was held with the objective to review evidence and create expert recommendations for clinicians when considering live viral vaccines post‐SOT. For consideration of VV and MMR post‐transplant, evidence exists only for kidney and liver transplant recipients. For MMR vaccine post‐SOT, consider vaccination during outbreak or travel to endemic risk areas. Patients who have received antiproliferative agents (eg. mycophenolate mofetil), T cell–depleting agents, or rituximab; or have persistently elevated EBV viral loads, or are in a state of functional tolerance, should be vaccinated with caution and have a more in‐depth evaluation to define benefit of vaccination and net state of immune suppression prior to considering vaccination. MMR and/or VV (not combined MMRV) is considered to be safe in patients who are clinically well, are greater than 1 year after liver or kidney transplant and 2 months after acute rejection episode, can be closely monitored, and meet specific criteria of "low‐level" immune suppression as defined in the document.